Comparison of the efficacy of 75 mg aspirin versus 150 mg aspirin for prevention of preeclampsia in patients at high risk for preeclampsia - Natasha Bushra; Wardah Saeed; Tayyaba Rashid; Mahwish Iqbal (Journal of University Medical & Dental College, 2024)
BACKGROUND & OBJECTIVE: Preeclampsia is a significant contributor to maternal health challenges. Emphasizing prevention over cure is a guiding principle in healthcare. As a reliable measure to forestall hypertension and its associated complications during pregnancy, aspirin is widely embraced. The early identification of risk factors plays a crucial role in the primary prevention of preeclampsia. Post-risk stratification, aspirin emerges as a pivotal player in the preventive strategy for individuals identified as high-risk for pre-eclampsia. To assess the effectiveness of 75 mg aspirin against 150 mg aspirin in preventing preeclampsia among individuals identified as having a high risk for the condition.METHODOLOGY: A quasi-experimental study was conducted in the Department of Obstetrics and Gynecology, Services Hospital, Lahore, from 27-12-2019 to 27-6-2020.240 patients were enrolled in the study, which was later divided into two groups. Group A received treatment with 75 mg aspirin, while Group B was administered 150 mg aspirin. Efficacy was determined based on whether blood pressure levels were below 140/90 mmHg, and proteinuria was rated as <+1 using the dipstick method.RESULTS: The mean age of the patients was 28.54±6.83 years, and the mean gestational age of the patients was 15.30±1.69 weeks. In the 75 mg group, the efficacy was achieved in 94(78.3%) patients, whereas in the 150 mg group, the efficacy was achieved in 108(90.0%) patients (p-value=0.013).CONCLUSION: This study concludes that the efficacy of 150 mg aspirin significantly surpasses that of 75 mg aspirin in preventing preeclampsia among high-risk pregnant patients.